2011
DOI: 10.4314/njbas.v19i1.69350
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Farmers (Women)’ Access to Agricultural Extension, Inputs and Credit Facility in Sabon-Gari Local Government Area of Kaduna State

Abstract: This study examines the accessibility of women to three main production inputs namely: Farm inputs (fertilizers, modern technology, improved seed etc), Credit facility and Contact with extension agents. Structured interview schedule, personal observation and analysis of records were used to collect information for the study. The findings revealed that women in the study area were engaged in farming activities such as crop production and rearing of livestock. Traditional technology is still the practice among w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Female farmers in the study area with larger farm income would access credit much easily than those whose incomes were low. This conforms to apriori expectation and in line with Owolabi, et al, (2011), that credit use is associated with higher income than average economic performance. The lending institution would prefer to grant credit facility to female farmers whose income is high because of higher chances of credit Nnamani, N. G and Iwezor-Magnus, D. N. default.…”
Section: Logit Estimate On the Determinants Of Credit Access Among Th...supporting
confidence: 90%
“…Female farmers in the study area with larger farm income would access credit much easily than those whose incomes were low. This conforms to apriori expectation and in line with Owolabi, et al, (2011), that credit use is associated with higher income than average economic performance. The lending institution would prefer to grant credit facility to female farmers whose income is high because of higher chances of credit Nnamani, N. G and Iwezor-Magnus, D. N. default.…”
Section: Logit Estimate On the Determinants Of Credit Access Among Th...supporting
confidence: 90%
“…For example, in Ethiopia the preference for female extension officers is explained by existing cultural barriers that discourage male extension workers from directly approaching married women farmers. Some studies have observed the restriction that cultural norms may have on women's access to extension services for as long as extension provision continues to be dominated by men (Oniang'o, 2005;Owolabi et al, 2011). Female extension officers are therefore likely to reach more women as has been suggested before (Chan, 2010).…”
Section: Assessment Of Extension Deliverymentioning
confidence: 88%
“…Women are also often denied equal access to productive resources like modern agricultural inputs, technologies and credit systems (FAO, 2011;Owolabi et al, 2011). In addition, key actors in agricultural production (FAO, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the tradition where farmers choose to have more children who can assist them in their work on the farm as it is common knowledge in traditional peasant agriculture, particularly in Nigeria, that children are the primary source of family labor. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 99%